MEMBANGUN KEPEDULIAN LINGKUNGAN EKOSISTEM BIRU MASYARAKAT PULAU MAITARA - Irmalita Tahir; Muhammad Aris; Rovina Andriani (Jurnal Abdi Insani, 2026)
The community service program titled Socialization of Building Awareness of Blue Ecosystem Conservation was carried out on Maitara Island, Tidore Islands City, with the aim of enhancing local fishers’ understanding of blue ecosystems as part of climate change mitigation and adaptation efforts. A participatory approach was applied through lectures, interactive discussions, and field practices involving 30 coastal community participants. Resource persons were drawn from the Provincial Marine and Fisheries Office, the Environmental Agency, Khairun University academics, and the Indonesian Forum for the Environment (WALHI) of North Maluku. The materials presented covered climate change concepts, the strategic role of blue ecosystems—such as mangroves, seagrass beds, and coral reefs—in carbon sequestration, and the importance of community participation in coastal ecosystem conservation. The results indicated an improvement in participants’ awareness and knowledge regarding the ecological and economic functions of blue ecosystems as natural coastal protection and fishery resource support systems. The activity also produced a Memorandum of Understanding (MoU) between the Maitara community, local government, academia, and environmental organizations as a joint commitment to preserve and manage blue ecosystems sustainably. Follow-up activities are recommended through continued mentoring and technology-based training for local fishers and community surveillance groups.